2008
DOI: 10.1155/2008/291808
|View full text |Cite
|
Sign up to set email alerts
|

(‐)‐Epigallocatechin Gallate Reduces Platelet‐Derived Growth Factor‐BB‐Stimulated Interleukin‐6 Synthesis in Osteoblasts: Suppression of SAPK/JNK

Abstract: We previously showed that the mitogen-activated protein (MAP) kinase superfamily, p44/p42 MAP kinase, p38 MAP kinase, and stress-activated protein kinase (SAPK)/c-Jun N-terminal (JNK), positively plays a part in the platelet-derived growth factor-BB- (PDGF-BB-) stimulated synthesis of interleukin-6 (IL-6), a potent bone resorptive agent, in osteoblast-like MC3T3-E1 cells while Akt and p70 S6 kinase negatively regulates the synthesis. In the present study, we investigated whether (-)-epigallocatechin gallate (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 34 publications
0
19
0
1
Order By: Relevance
“…The bioactive components in tea may benefit bone health in terms of maintaining a higher bone mineral density57, 58 ) . Furthermore, green tea or its bioactive EGCG component has been shown to reduce RA via an improvement in the bone resorption process, which ultimately reduces the release of both NTX and DPD in serum or urine samples59,60,61 ) . The high EGCG contents of our green tea extract were shown to be responsible for the anti-rheumatic and other biological activities of green tea, and EGCG possesses about 25–100 times more antioxidant potential than vitamins C and E62,63,64 ) .…”
Section: Discussionmentioning
confidence: 99%
“…The bioactive components in tea may benefit bone health in terms of maintaining a higher bone mineral density57, 58 ) . Furthermore, green tea or its bioactive EGCG component has been shown to reduce RA via an improvement in the bone resorption process, which ultimately reduces the release of both NTX and DPD in serum or urine samples59,60,61 ) . The high EGCG contents of our green tea extract were shown to be responsible for the anti-rheumatic and other biological activities of green tea, and EGCG possesses about 25–100 times more antioxidant potential than vitamins C and E62,63,64 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Both epidemiological [22][23][24][25], animal [10,11] and cellular [26][27][28] studies strongly suggested that green tea polyphenols (GTP, green tea extract) are a promising dietary antioxidant for preventing bone loss in women and men with low bone mass [21]. In addition, our recent study shows that drinking water supplemented with GTP mitigated bone loss due to an increase of antioxidant capacity in conjunction with a decrease in oxidative stress damage [10].…”
Section: Introductionmentioning
confidence: 93%
“…The Wnt pathway is now known to control bone development and bone mass acquisition at all skeletal sites [130, 131], and Wnt signaling drives differentiation of osteo-chondrogenic progenitor cells toward the osteoblast lineage. When the Wnt ligand binds to its receptor (Frizzled) and co-receptor (low-density lipoprotein receptor-related protein [LRP)5/6] [160-162], the signal turns on the Wnt pathway [133], giving the power of Wnt signaling to stimulate osteoblastic differentiation.…”
Section: Possible Mechanisms Of Green Tea On Osteo-protectionmentioning
confidence: 99%
“…These same authors [159] also reported that EGCG inhibits basic-fibroblast-growth-factor-2-induced IL-6 synthesis at least partly via attenuation of the p44/p42 MAP kinase pathway and the p38 MAP kinase pathway in osteoblasts. Takai et al [160] found that EGCG significantly reduced the IL-6 synthesis and IL-6 mRNA expression induced by platelet-derived growth factor-BB through suppression of the SAPK/JNK pathway in osteoblast-like MC3T3-E1 cells. Moreover, Ishida [161] reported that EGCG controls inflammatory bone resorption in chronic osteomyelitis by inhibiting the production of IL-6 and RANKL in osteoblasts infected with S. aureus .…”
Section: Possible Mechanisms Of Green Tea On Osteo-protectionmentioning
confidence: 99%